2012
DOI: 10.1002/cta.1840
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and design of a two‐transformer active‐clamping ZVS isolated inverse‐SEPIC converter

Abstract: SUMMARY This paper presents a two‐transformer active‐clamping zero‐voltage‐switching (ZVS) isolated inverse‐SEPIC converter, which is mainly composed of two active‐clamping ZVS isolated inverse‐SEPIC converters. The proposed converter allows a low‐profile design for liquid crystal display TVs and servers. The presented two‐transformer active‐clamping ZVS isolated inverse‐SEPIC converter can equally share the total load current between two secondaries. Therefore, the output inductor copper loss and the output d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The equivalent circuit of this mode is shown in Figure 3D, where the S 3 switch is turned on in the ZVS condition. In this mode, the i Lm1 , i Ls1 , and i ℓ1 currents can be calculated from (4), (5), and (6), respectively. By considering 4 and 5, i S1 can be obtained as follows:…”
Section: Boost Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…The equivalent circuit of this mode is shown in Figure 3D, where the S 3 switch is turned on in the ZVS condition. In this mode, the i Lm1 , i Ls1 , and i ℓ1 currents can be calculated from (4), (5), and (6), respectively. By considering 4 and 5, i S1 can be obtained as follows:…”
Section: Boost Operationmentioning
confidence: 99%
“…In this converter, the switched-capacitor modules have to be operated at high switching frequency; consequently, the switching losses would be increased. In previous studies, [5][6][7][8] some isolated dc-dc converters with soft switching capabilities that are suitable for electric vehicle applications are presented. However, these converters can only be operated in boost mode, and they suffer from high input current ripples.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that in operation at the duty cycle range 1/3 ≤ D < 2/3, the maximum current ripple value of the proposed topology is 0.0083 occurs at D = 1/2, where this value is one‐third compared with Jin and Liu 23 and half value compared with Bal et al 51 While in operation at duty cycle range 2/3 ≤ D < 1, the current ripple of studied topology is higher than that of the converter in Bal et al 52 ; when the duty cycle is equal to 5/6, and the normalized current ripple is equal to 0.0083. Furthermore, the current ripple of the previously proposed converters in previous studies 26 , 51 is higher than that of the proposed topology, according to the values shown in Figure 12A. Also, the normalized current ripple cancellation of the proposed topology occurs when the duty cycle is 1/3 and 2/3, which means that the proposed topology has a better dynamic response and smaller size inductor.…”
Section: Mathematical Analyses and Fundamental Equationsmentioning
confidence: 82%
“…The dc voltage gain of NTBDCs is significantly limited; however, the dc voltage gain of ITBDCs is achieved by adjusting the transformer turns ratio; however, using high voltage transformers with a large number of turns also can introduce several problems, for instance, the leakage inductance and the parasitic capacitance of the transformer may cause voltage and current spikes, increased losses, and noises that degrade the converter performance. To overcome the previous disadvantages of the converters based on the transformer, the clamp circuit techniques are introduced to recycle the energy stored in the leakage inductance and absorb the voltage spikes on the main switch 38–45 . Although of drawback, the galvanic isolation has the following advantages: These are necessary for many industrial applications; the electrical grounds of the two electrical systems may be at different potentials; personnel safety; increases the filter's operation frequency; noise reduction; and correct operation of protection systems are the main reasons behind galvanic isolation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation